Dampak Pengimplementasian Kurikulum 2013 terhadap Performa Siswa Sekolah Menengah Pertama - Sutjipto -- (Jurnal Pendidikan dan Kebudayaan, 2014)
The purpose of this study is to determine the contribution of principal transformational leadership, teaching performance of teachers, and the learning culture towards achievement of madrasah aliyah. Correlational survey is used as the method of the research with 274 sample of teachers .The sampling techniques used are area sampling, proportional sampling and random sampling. Questionnaire used as the instrument to be analyzed by using descriptive and inferential statistics. The results of this study indicate: 1) the level of achievement of the madrasah, principal transformational leadership, teaching performance of teachers and learning culture is good; 2) transformational principal leadership contributes positively and significantly towards achievement of madrasah aliyah; 3) teacher performance in teaching contributes positively and significantly towards achievement of madrasah aliyah; 4) learning culture contributes positively and significantly towards achievement of madrasah aliyah: 5) transformational principal leadership, teacher performance in teaching and learning culture contribute positively and significantly towards achievement of madrasah aliyah. Accordingly, increasing the principal transformational leadership, teaching performance of teachers and the culture of learning leads to the improvement of madrasah achievement.